Edukasi Pengelolaan Arsip Bagi Pengurus OSIS SMK Ma’arif NU Doro Kabupaten Pekalongan - Aria Mulyapradana; Ary Dwi Anjarini; Febby Restu Anggita; Asyarotun Asyarotun; Siti Zumrotul Chusna; Mutiara Hafsah Zein; Najma Varadifa; Nida Sunniyah (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Archives for organizations or institutions have a role as a center for reminders, decision making, evidence and supervision, but many organizations or institutions have not maximized in records management and lack of awareness of archives so that it has an impact on retrieval of archives that are quite long and found to lose records resulting in decreased organizational performance and service quality. To overcome the condition, the Community Service Team held archive management training activities as a form of contribution to the community and helped partners overcome problems faced in organizations or institutions. The activity partners are 25 people from the Student Council Board of SMK Ma'arif NU Doro Pekalongan Regency. The method used is participatory and the material is delivered using the lecture method. This activity was welcomed by the Principal, Student Council Supervisor and Student Council Administrator because it could increase knowledge and skills for Student Council administrators in archive management. The student council board is very enthusiastic about participating in a series of activities and it is hoped that this activity can be sustainable.